"A hybrid approach for GISTs near the esophagogastric junction, a case report". (February 2021) - Aguayo, William G.; Rojas, Christian L.; Molina, Gabriel A.; Cárdenas, B. Andrés; Parreño, Emilio F.; Melendez, Sergio D.; Alvarez, Monica P.; Basantes, Veronica M.; Aguayo, Johan J.; Gualotuña, Fatima V.
Abstract: Introduction and importance: Gastrointestinal stromal tumors are the most frequent mesenchymal tumors of the gastrointestinal tract. Complete resection of GISTs is the only chance of cure for patients. When these tumors are located near the esophagogastric junction, the surgical risk can cause deformity or stenosis in the gastric inlet, leading to higher complications and diminishing their quality of life. In such cases, a more sophisticated and tailored approach should be used. Case presentation: We present the case of a 42-year-old female; she presented to our office with a 3-year history of nausea, vomiting and abdominal distension. Two GISTs were located near the EGJ, and with a combined approach we achieved complete resection. On follow-ups, the patient is doing well. Clinical Discussion, Conclusion: When diagnosis is confirmed, surgical resection must be the first choice for GISTs as complete surgical excision is the only permanent cure. The rise of endoscopic surgery has become a valuable tool and a critical element in surgery. Hybrid techniques that combine laparoscopic and endoscopic approaches can improve the patient's outcomes and provide better results. Highlights: The rise of endoscopic surgery has become a valuable tool and a critical element in surgery. Early histologic diagnosis and surgical resection is the most reliable way to improve patients' quality of life. The surgical decision will be what define the future of the patient and, ultimately, his life.